28P RNA-seq based transcriptome profiling provides important insights into progression of gastric cancer. (15th December 2019) - Verma, R
Abstract: Background: Gastric cancer (GC), ranking fifth among cancers, is the third most common cause of cancer related mortality in the world. The symptoms of GC occur rather in the late stages, making early diagnosis a challenging task to clinicians compromising disease management. Therefore, efforts are underway to develop effective biomarkers for early diagnosis of the disease and to identify potential targets for drug development. Methods: Illumina RNA-Seq based transcriptome profiles of six tumor and normal tissue pairs at different stages (stage I, II and III) of GC were generated to identify differentially expressed genes (DEGs) and single nucleotide polymorphisms (SNPs) implicated in gastric tumorigenesis. The major clusters of candidate genes at different stages of GC and associated enriched gene ontology terms were analysed. Transcription factors involved in GC were also identified and the protein-protein interaction networks were constructed. Results: A total of 2207 differentially expressed genes including 972 upregulated genes and 1235 downregulated genes were identified covering stage I, II and III of disease progression. The SNP profiles revealed gene enrichment in cancer related pathways including apoptosis, mTOR and MAPK signalling. The DEGs were accommodated in various ontology categories primarily with digestion system and digestive tract development processes. Functional enrichment of SNPs showed GO categories such as immune system process, regulation of signalling, response to stress, transport, etc. Furthermore, 18 upregulated and 21 downregulated transcription factors were identified during cancer progression. Conclusion: Stage-specific identification of DEGs and transcription factors may help in the better understanding of the molecular pathogenesis of gastric cancer. Our findings will also provide useful leads for developing future strategies for the management of gastric cancer. Legal entity responsible for the study: The author. Funding: Defence Institute of Physiology & Allied Sciences (DIPAS), Defence Research and Development Organisation (DRDO). Disclosure: The author has declared no conflicts of interest.